Proceedings of the International Congress on Information and Communication Technology ICICT 2015, Volume 2 - Satapathy, Suresh Chandra; Bhatt, Yogesh Chandra; Joshi, Amit.; Mishra, Durgesh Kumar; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2016)
This volume contains 69 papers presented at ICICT 2015: International Congress on Information and Communication Technology. The conference was held during 9th and 10th October, 2015, Udaipur, India and organized by CSI Udaipur Chapter, Division IV, SIG-WNS, SIG-e-Agriculture in association with ACM Udaipur Professional Chapter, The Institution of Engineers (India), Udaipur Local Centre and Mining Engineers Association of India, Rajasthan Udaipur Chapter. This volume contains papers mainly focused on ICT for Managerial Applications, E-governance, IOT and e-Mining.
Chapter 1. A Novel Methodology to Detect Bone Cancer Stage Using Mean Intensity of MRI Imagery and Region Growing Algorithm -- Chapter 2. Firefly Algorithm Hybridized with Flower Pollination Algorithm for Multimodal Functions -- Chapter 3. BCI for Comparing Eyes Activities Measured from Temporal and Occipital Lobes -- Chapter 4. An Adaptive Edge-preserving Image Denoising Using Block-based Singular Value Decomposition in Wavelet Domain -- Chapter 5. Performance Analysis of Voltage Controlled Ring Oscillators -- Chapter 6. Modified Design of Integrated Ultra Low Power 8-bit SAR ADC Architecture Proposed for Biomedical Engineering (Pacemaker) -- Chapter 7. A Novel Symmetric Key Cryptography Using Dynamic Matrix Approach -- Chapter 8. Experimenting Large Prime Numbers Generation in MPI Cluster -- Chapter 9. Design and Analysis of High Performance CMOS Temperature Sensor Using VCO -- Chapter 10. High Performance Add Drop Filter Based on PCRR for ITU-T G.694.2 CWDM System -- Chapter 11. Efficient Data Dissemination in Wireless Sensor Network Using Adaptive and Dynamic Mobile Sink Based on Particle Swarm Optimization -- Chapter 12. A New Approach to Intuitionistic Fuzzy Soft Sets and its Application in Decision Making -- Chapter 13. Categorical Data Clustering Based on Cluster Ensemble Process -- Chapter 14. Region Based Clustering Approach for Energy Efficient Wireless Sensor Networks -- Chapter 15. Analyzing Complexity Using a Proposed Approximation Algorithm MDA in Permutation Flow Shop Scheduling Environment -- Chapter 16. Empirical Evaluation of Threshold and Time Constraint Algorithm for Non-replicated Dynamic Data Allocation in Distributed Database Systems -- Chapter 17. Automated Usability Evaluation of Web Applications -- Chapter 18. An Efficient Approach for Frequent Pattern Mining Method Using Fuzzy Set Theory -- Chapter 19. Virtual Machine Migration: A Green Computing Approach in Cloud Data Centers -- Chapter 20. Detecting Myocardial Infarction by Multivariate Multi-scale Covariance Analysis of Multi-lead Electrocardiograms -- Chapter 21. QoS Improvement in MANET Using Particle Swarm Optimization Algorithm -- Chapter 22. Comparing Various Classifier Techniques for Efficient Mining of Data -- Chapter 23. Fingerprint Recognition System by Termination Points Using Cascade Forward Back Propagation Neural Network -- Chapter 24. On the Dynamic Maintenance of Spanning Tree -- Chapter 25. Internet of Things Future Vision -- Chapter 26. Design and Analysis of Energy Efficient Opamp for Rectifier in Micro Scale Energy Harvesting (Solar Energy) -- Chapter 27. Design and Analysis of Various Charge Pump Schemes to Yield Solar Energy under Various Sunlight Intensities -- Chapter 28. Performance Evaluation of Speech Synthesis Techniques for English language -- Chapter 29. Systematization of Reliable Network Topologies Using Graph Operators -- Chapter 30. Network Performance analysis of Start-up Buffering for Live Streaming in P2P VOD Systems for Mesh Based Topology -- Chapter 31. Cryptanalysis of Image Encryption Algorithms Based on Pixels-Shuffling and Bits-Shuffling -- Chapter 32. Circular-Shape Slotted Microstrip Antenna -- Chapter 33. Energy Efficient Data Aggregation Technique Using Load Shifting Policy for Wireless Sensor Network -- Chapter 34. Architectural outline of GIS Based Decision Support System for Crop Selection -- Chapter 35. Retrieving Instructional Video Content from Speech and Text Information -- Chapter 36. Performance improvement of SLM Based MC-CDMA System Using MIMO Technique -- Chapter 37. SNR Improvement for Evoked Potential Estimation Using Wavelet Transform Averaging Technique -- Chapter 38. A GIS and Agent Based Model to Simulate Fire Emergency Response -- Chapter 39.Analyzing Link Stability and Throughput in Ad Hoc Network for Ricean Channel by Varying Pause Time -- Chapter 40. A Review on Pixel Based Binarization of Gray Images -- Chapter 41. Mobility and Energy Conscious Clustering Protocol for Wireless Networks -- Chapter 42. RE2R- Reliable Energy Efficient Routing for UWSNs -- Chapter 43. Mitigation Techniques for Gray Hole and Black Hole Attacks in Wireless Mesh Network -- Chapter 44. Investigation for Land Use and Land Cover Change Detection Using GIS -- Chapter 45. Effectiveness of Computer Based Instructional Visualization and Instructional Strategies on E-learning Environment -- Chapter 46. Test Case Reduction Using Decision Table for Requirements Specifications -- Chapter 47. Resource Management Using ANN-PSO Techniques in Cloud Environment -- Chapter 48. Congestion Control in Heterogeneous Wireless Sensor Networks for High Quality Data Transmission -- Chapter 49. Robust Data Model for Enhanced Anomaly Detection -- Chapter 50. Database Retrieval Based Digital Watermarking For Educational Institutions -- Chapter 51. Conceptual Modelling Through Fuzzy Logic for Spatial Database -- Chapter 52. Performance Analysis of Clustering Algorithm in Sensing Micro-blog for Smart Cities -- Chapter 53. Offloading for Application Optimization Using Mobile Cloud Computing -- Chapter 54. Integration of Color and MDLEP as a Feature Vector in Image Indexing and Retrieval System -- Chapter 55. Reversible Data Hiding through Hamming Code Using Dual Image -- Chapter 56. A Hybrid Fault Tolerant Scheduler for Computational Grid Environment -- Chapter 57. Image Transmission in OSTBC MIMO-PLC over Nakagami-m Distributed Background Noise -- Chapter 58. Optimized Relay Node Based Energy Efficient MAC Protocol for a Wireless Sensor Network -- Chapter 59. Reliable & Prioritized Data Transmission Protocol for Wireless Sensor Networks -- Chapter 60. Caching: QoS enabled Metadata Processing Scheme for Data Deduplication -- Chapter 61. Design and Analysis of Grid Connected Wind/PV Hybrid System -- Chapter 62. Requirements Prioritization - Survey and Analysis -- Chapter 63. GPU Acceleration of MoM for Computation of Performance Parameters of Strip Dipole Antenna -- Chapter 64. Energy Saving Model Techniques in Wireless Ad-hoc Network -- Chapter 65. Multi-Region Pre-Routing in Large Scale Mobile Ad-hoc Networks (MRPR) -- Chapter 66. Design Analysis of an n-bit IFSR Based Generic Stream Cipher and its Implementation Discussion on Hardware and Software Platforms -- Chapter 67. An Effective Strategy for Fingerprint Recognition based on pRAM's Neural Nature with Data Input Mappings -- Chapter 68. Various E-governance Applications, Computing Architecture and Implementation Barriers -- Chapter 69. Fuzzy Logic Based Expert System for Assessment of Bank Loan Applications in Namibia.
Keywords: Telecommunication; Data mining; Data protection; Communications Engineering, Networks; Data Mining and Knowledge Discovery; Data and Information Security